Działalność duszpasterska i społeczna pastora Rudolfa Gustawa Gundlacha (1850–1922). Przyczynek do historii dobroczynności w Łodzi - Sosnowska, Joanna (Studia z Historii Społeczno-Gospodarczej XIX i XX Wieku, 2012)
Rudolf Gustaw Gundlach was born on June 21, 1850 in Paproć Duża near Łomża, located then in the Augustów Governorate. He was raised in an evangelical family which cultivated Protestant ethical traditions. Having left a German secondary school in Warsaw in 1870, he started studying in the Faculty of Theology of the University of Dorpat. On April 18, 1875, he was appointed as an Evangelical clergyman and started working in the Holy Trinity Lutheral Church in Warsaw. Other centres of his pastoral work included parishes in Kamień near Chełm (1876–1889), Wiskitki near Żyrardów (1889–1898), and Łódź (1898–1922). Taking the function of the parish priest in the Holy Trinity Lutheral Church in Łódź in Nowy Rynek (Plac Wolności now), the Reverend R. Gundlach conducted energetic social activities apart from his everyday responsibilities related to pastoral work. He strived to help the poor and the needing, regardless from their religion and nationality. It is worth mentioning that, at the turn of the 19th and 20th centuries, Łódź was a multinational city, with population diversified in terms of religion and culture. The community at risk of poverty and no social care included the working class families. For 13 years, since 1907, the Reverend R. Gundlach was the chairman of the philantropic organisation called Łódzkie Chrześcijańskie Towarzystwo Dobroczynności [Łódź Christian Charity Society], which conducted its activities in Łódź in 1885–1940. Together with members and activists of the Society, R. Gundlach organised 17 philantropic institutions for adults and children, including hospitals, clinics, orphanages, schools, tea houses, job centres, old people’s homes, and night shelters. The Reverend Rudolf Gundlach cooperated permanently with the monthly titled “Zwiastun Ewangeliczny”, where he published his works on religious and social issues. He died in Łódź on October 11, 1922.